2017
DOI: 10.1016/j.chemosphere.2017.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of trace metals (Cu, Pb, Ni, Zn) between particulate, colloidal and truly dissolved fractions in wastewater treatment

Abstract: The distribution of Cu, Pb, Ni and Zn between particulate, colloidal and truly dissolved size fractions in wastewater from a trickling filter treatment plant was investigated. Samples of influent, primary effluent, humus effluent, final effluent and sludge holding tank returns were collected and separated into particulate (i.e. > 0.45 μm), colloidal (i.e. 1 kDa to 0.45 μm), and truly dissolved (i.e. < 1 kDa) fractions using membrane filters. In the influent, substantial proportions of Cu (60%), Pb (67%), and Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 33 publications
1
46
1
Order By: Relevance
“…Except for As and Zn, which are distributed equally between the two fractions, all other metal species are principally distributed in the NP fraction. These results confirm the high affinity of metal species with carbon-based colloids generally observed in the environment (Dai et al, 1995; M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT Hargreaves et al, 2017;Sau et al, 2010;Waeles et al, 2008). A recent work from Hargreaves et al showed that wastewater effluent contained a considerable distribution of metal (Cu, Pb, Ni and Zn) in the nanoscale fraction adsorbed and/or complexed with non-humic macromolecules, such as soot nanoparticles (Hargreaves et al, 2017).…”
Section: Accepted Manuscript 11supporting
confidence: 76%
“…Except for As and Zn, which are distributed equally between the two fractions, all other metal species are principally distributed in the NP fraction. These results confirm the high affinity of metal species with carbon-based colloids generally observed in the environment (Dai et al, 1995; M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT Hargreaves et al, 2017;Sau et al, 2010;Waeles et al, 2008). A recent work from Hargreaves et al showed that wastewater effluent contained a considerable distribution of metal (Cu, Pb, Ni and Zn) in the nanoscale fraction adsorbed and/or complexed with non-humic macromolecules, such as soot nanoparticles (Hargreaves et al, 2017).…”
Section: Accepted Manuscript 11supporting
confidence: 76%
“…4 panels a and b, respectively). Studies (Hargreaves et al 2017(Hargreaves et al , 2018 have reported that these metals are mainly bound to particulate and colloidal materials that readily adsorb to the surface of flocs. Hence, elimination of Cu and Pb by CF was expected.…”
Section: Metalsmentioning
confidence: 99%
“…Conversely, Ni and Zn abound in the soluble fraction, which requires adsorption/ion exchange processes or chemical modification for their effective elimination (Martin et al 1995). Such two-fraction distinction has been challenged by recent findings (Worms et al 2010;Hargreaves et al 2017Hargreaves et al , 2018) that indicate metals can adsorb or complex with organic material within the colloidal size fraction (1 kDa-0.45 µm). Such findings suggest that technologies capable of removing particles within the colloidal fraction have good potential to enhance metals removal from wastewater (Hargreaves et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this study, SHS molecular weight less than 1 kDa was designated as the low molecular weight SHS (LMHS), and the molecular weight higher than 1 kDa was designated as the high molecular weight SHS (HMHS). It is worth noting that the LMHS still contained various heavy metal species (free ion metals, binding with low molecular weight SHS) [17,18,19,20,21,22,23]. Moreover, the low molecular weight DOM and SHS had a metal and hydrophobic organic compound binding capacity [24,25,26].…”
Section: Introductionmentioning
confidence: 99%